Economic land evaluation for agricultural resource management in Northern Thailand - Chalermpol Samranpong (2018)
This paper describes a GIS-based system, EconSuit, that supports dynamic assessment of economic land suitability for major economic crops in Northern Thailand. Prior to economic land evaluation, a physical land suitability index is computed using a fuzzy set approach in GIS. The procedure bypasses crop modeling and permits suitability to be defined in a continuous scale with a graphic interface enabling a user to dynamically assign diagnostic factors and weights for physical land evaluation. Economic land evaluation is accomplished by assigning field survey data to land mapping units using spatial interpolation. Unit costs of inputs and outputs can be entered through the graphic user interface, allowing constant updates of economic values in the system. Scenarios of agricultural land use planning may be formulated by users depending on policy or economic circumstances. © 2009 Elsevier Ltd. All rights reserved.